Collective action frames and the developing role of discursive practice in worker organisation: the case of OUR Walmart. (1st April 2018) - ,
Abstract : Recent technological innovations have made possible a range of new communication practices among workers engaged in struggles to raise wages and improve working conditions. New forms of social organisation and association are changing how collective action is carried out and how collective action frames are generated. Looking at a year's worth of content from a secret Facebook group designed as a forum for current and former Walmart employees, this study considers how communication practices relate to the organisational forms of coping and resistance among workers. Analysis of the posts and comments transpiring within the group, which is loosely affiliated with the Organisation United for Respect at Walmart (OUR Walmart), suggests a growing role for personalised forms of communication in the production and circulation of collective action frames. These forms blur the distinction between discursive and strategic communication processes, requiring us to reconsider the roles traditionally played by social movement organisations and rank-and-file participants. The primary contribution of this research is to demonstrate how emerging communication practices problematise distinctions between communities of coping and of resistance, between activities that are personally satisfying and those that prioritise group concerns, and between the self-organised activities of employees and the actions of labour unions. The article concludes with a consideration of the implications of these emerging communication practices for movement outcomes.